2020
DOI: 10.4236/aim.2020.107023
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Antibiotic-Resistant Fecal Coliforms in the Stream of a Sewage Treatment Plant in Tokyo

Abstract: We are confronting a new threat in the prevalence of antibiotic-resistant bacteria followed by epidemic spread in aquatic environments in metropolitan areas because damage from river floods is increasing remarkably in Japan due to global extreme weather. The sewer penetration rate is about 100% in Tokyo and reclaimed water from sewage treatment plants accounts for over 50% of all water in both the down-and mid-stream areas of local rivers. The water quality of these rivers, which contain microflora, seems to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Being a conjugative plasmid, IncF is related to the dissemination of bla CTX-M-15 by horizontal gene transfer. 98,99 exemplary studies show how activated sludge from wastewater treatment plants can be a source of high prevalence of CTX-M as demonstrated in Japan, 100 Austria, 101 and India. 102 The E. coli clones ST131 and ST10 were found across South America (Supplementary Table 3).…”
Section: Dovepressmentioning
confidence: 99%
“…Being a conjugative plasmid, IncF is related to the dissemination of bla CTX-M-15 by horizontal gene transfer. 98,99 exemplary studies show how activated sludge from wastewater treatment plants can be a source of high prevalence of CTX-M as demonstrated in Japan, 100 Austria, 101 and India. 102 The E. coli clones ST131 and ST10 were found across South America (Supplementary Table 3).…”
Section: Dovepressmentioning
confidence: 99%
“…Environmental studies based on the analysis of bacterial strains during the treatment process most often concern the most critical pathogens posing the greatest threat, mainly Enterobacterales . In the reviewed literature, the predominantly tested and detected species among this bacteria family were Escherichia coli and K. pneumoniae [ 67 , 68 , 71 , 72 , 74 , 77 , 78 , 79 , 81 , 83 , 85 , 99 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 ]; however, different species of Citrobacter spp., Enterobacter spp., Pseudomonas spp., Aeromonas spp., or others were noted as well [ 71 , 76 , 80 , 87 , 92 , 102 , 104 , 109 , 110 , 121 , 126 , 127 , 128 ].…”
Section: Clinically Significant β-Lactam Resistance Genes In Wastewat...mentioning
confidence: 99%
“…Concerning the removal of class A β-lactam ARGs, there is no universal target panel in qPCR studies; however, it has been noted that, although the WWTPs could effectively eliminate examined genes, their abundance was still reported in effluents and receiving water bodies. For example, in the study of Schages et al, strains harboring bla CTX-M were isolated from the effluent [ 123 ], as well as in a Japanese study wherein strains possessing ARGs belonging to the bla CTX-M-1 , bla CTX-M-9 , bla TEM , and bla SHV families survived even after sterilization [ 124 ]. Other studies reported similar results of the ARGs’ presence in effluent samples [ 108 , 135 , 136 , 137 , 138 ].…”
Section: Clinically Significant β-Lactam Resistance Genes In Wastewat...mentioning
confidence: 99%